A Prospective study of the Glasgow-Blatchford score performance in predicting clinical outcomes in patients with upper GI bleeding, in rural India - Sanjot B. Kurane; Subodh P. Ugane (International Journal of Medical Research and Review, 2016)
Introduction: Many patients present to the emergency department with varying grades of UGI bleed, so deciding whether a patient requires emergency endoscopy or managed on out patient basis is a challenging decision. The Glasgow-Blatchford Score (GBS) is an easy score to calculate and identifies patients who are a high risk.Methods: This was a prospective study. The data of adult patients presenting with upper GI bleeding were included in this study. A GBS was calculated for each patient based on clinical or laboratory variables at the time of presentation. The outcome of the patient was observed, and patients were divided in two groups i.e. high and low risk.Univariate analysis was performed to compare these two groups.Results: Total 86 patients with UGI bleeding were included in the study. Amongst them 88% were males and 12% females. Out of 86 patients, 38 patients were included in low risk group, and 48 patients were in high-risk group Mean Glasgow Blatchford Scoring scores were 5.94 for 38 low-risk subjects and 10.16 for 48 high-risk patients. The sensitivity and specificity were 100% and 36.82% respectively, for a cut-off value of GBS score > 3, 95.83% and 63.15% for a cut-off value of GBS score >5, and 91.66% and 73.68% for a cut-off value of GBS >7.Conclusion: The Glasgow-Blatchford score is based on simple clinical and laboratory variables, which helps in risk stratification [High risk / low risk] of the patients presenting with upper GI bleed, in the emergency department.